Physical activity of 15-17 years old adolescents in different educational settings: a Polish-Czech study - Frömel, Karel; Groffik, Dorota; Chmelík, František; Cocca, Armando; Skalik, Krzysztof (Central European journal of public health, 2018)
OBJECTIVES: The aim of this study was to analyze adolescents' physical activity (PA) in two different educational settings, and to estimate the association between meeting PA recommendations and specific characteristics of adolescents' lifestyle. METHODS: The study was carried out in the Moravia region of the Czech Republic and in the Silesia-Opole region of Poland. In total, 1,846 participants completed the long International Physical Activity Questionnaire (IPAQ-long) using the online Indares system. RESULTS: Results showed that the Polish sample was significantly more physically active than the Czech one concerning school PA (p < 0.001; η2 = 0.07). Comparing by gender, significant differences were found in vigorous PA (p < 0.001; η2 = 0.05) and moderate PA (p < 0.001; η2 = 0.08) in both samples. The recommendations for vigorous PA are met by 45.9% of Czech boys and 33.4% of girls; and by 64.5% of Polish boys and 51.3% of girls. Participation in organized PA was the main correlate to achieve the recommendations of vigorous PA in both Czech (p < 0.001; CI = 4.47-9.25) and Polish adolescents (p < 0.001; CI = 1.99-5.37). CONCLUSIONS: The Polish educational model seems to be more effective for enhancing higher levels of PA among youth, as it provides pupils with a wider offer of organized PA. Girls were found to be less active than boys at high PA intensities in both countries, therefore, more effort must be put on involving them in organized PA.
Keywords: Schools; ženské pohlaví; mladiství; cvičení; Surveys and Questionnaires; lidé; Česká republika; Life Style; Polsko; Exercise; Humans; sports; secondary school; průzkumy a dotazníky; Czech Republic; Poland; mužské pohlaví; health; Male; školy; Adolescent; physical education; Internet; Female; životní styl